Synbion and United Agarwood Planters, Inc. seal agreement to develop the Agarwood industry with new discovery products - Naqiah, Puaad (UMPSA, 2024)
KUALA LUMPUR, 12 September 2024 – UMPSA Holdings Sdn. Bhd.’s spin-off company, Synbion, and United Agarwood Planters, Inc. (UAP), based in the Philippines, signed a Memorandum of Agreement (MoA) to enhance their collaboration in the agarwood (agaru) industry using scientifically based new discovery products.